Perimenopausal Pneumococcal Tubo-Ovarian Abscess - a Case Report and Review - Srividya Seshadri; John Kirwan; Tim Neal (Hindawi Limited, 2004)
Background: Genital tract infections in females secondary to Streptococcus pneumoniae (pneumococcus) are unusual. Tubo-ovarian abscess resulting from such an infection is a rare occurrence and diagnosis is not always easy. This report demonstrates the problems of recognizing this condition and summarizes the pathomechanism, investigations leading to a diagnosis and the subsequent management.